Natural facelift longevity: A unique observation in a deep plane facelift case series - Brian P Dickinson; Peter F Giacobazzi (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Background: Facelift procedures are technically challenging and are difficult procedures to consistently achieve good results. Critical evaluation of one's facelift results in their practice over time is helpful to evaluate progress and to find areas to improve upon so that we can optimize patient results. We evaluated our charts and before and after photographs to improve our quality and examined healing time and long term results. During our review, we discovered a unique observation where we compared the deep plane facelift results to subcutaneous or limited Superficial Musculoaponeurotic System (SMAS) facelifts.  Methods: A retrospective chart review was conducted on all patients who underwent deep-plane facelift by the junior author between 2008 and 2020 and the senior author between 1978 and 2015. Patient satisfaction was measured subjectively in chart review. During the course of the review, so the junior author could learn, the junior author reviewed the senior author's results. In the learning process, we encountered four patients who underwent a subcutaneous or limited SMAS facelift years prior to their deep-plane rhytidectomy and then compared the photographs with regard to the neck, jowls, nasolabial folds, and malar fat pad at an equivalent interval post-op deep plane facelift. In this manner the patient served as their own internal control and the deep plane had actually been performed later in life. Results:  The recovery time was comparable to subcutaneous or SMAS facelifts. Four patients had undergone a deep plane facelift and a prior subcutaneous or limited SMAS facelift. The follow-up ranged from 3 to 10 years post deep plane facelift. Photographic comparison consisted of the pre-operative deep plane photograph which was also frequently defined as the time post-operatively from the patient's previous subcutaneous or limited SMAS facelift. The deep plane facelift appeared to have maintained correction over time with regard to the neck, jowls, nasolabial folds, and malar fat pad at an equivalent or greater time interval despite the patient being older.  Conclusion: The deep plane facelift is a safe and durable method to address the aging changes of the neck, jowls, nasolabial fold, and malar fat pad. The technique is helpful to avoid a previously created surgical plane in secondary facelifts. We present a unique observation in this series where the deep plane technique tended to show long lasting results when compared to the subcutaneous facelift in the same individual.